Let’s Campaign for a Fairer Society in the Aftermath of COVID-19 - Scambler, Graham (Frontiers in Sociology, 2022)
In this paper I ground a brief account of the impact of COVID-19 on the United Kingdom in an understanding of a decade of austerity politics from 2010 to 2020, itself a product of the advent and consolidation of post-1970s financialised or rentier capitalism. I argue that such an analysis is essential if realistic plans are to be laid for a ‘better’ – understood here as a more equitable or ‘fairer’ – society. I go on to consider the contributions that sociology can, and arguably should, make to this end. This involves a range of engagements from scholarship at one end of the spectrum to action or muckraking sociology at the other. In addition to plotting a role for sociology, I suggest a set of criteria for recognizing a ‘fairer society’; postulate a series of institutional reforms that might characterize the attainment of such a society; and outline and confront social structural, cultural and agential obstacles to its realization. A theme running throughout the paper is that the delineation and promulgation of the ‘good society’ remains central to any credible - that is, post-Enlightenment reconstruction of - the sociological project.